Comparative Analysis of Financial Performance of Indonesian Syariah Banks and Malaysian Syariah Banks Based On the GCG (Good Corporate Governance) Approach for the Period 2020-2023 - Beti Sri Bakti; Mukhzarudfa Mukhzarudfa; Muhammad Ridwan (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2025)
Research This aiming For test and analyze difference performance Indonesian Islamic bank finance with Malaysian Islamic banks seen based on GCG (Good Corporate Governance). GCG (Good Corporate Governance) is assessed using the Board of Commissioners Independent , Ownership Institutional , Ownership Managerial , Foreign Ownership , Audit Committee , Board of Directors and Sharia Supervisory Board . Financial performance measured with Return on Assets (ROA) Ratio . Research This is study quantitative , and the sources of data obtained namely secondary data . Population study This is banking sharia in Indonesia and Malaysia. Research sample totaling 8 banks sharia , 4 Indonesian sharia banks and 4 Malaysian sharia banks with use report finance every year and have complete data with variables used during 2020-2023 . Retrieval sample research determined with purposive sampling technique . Variables dependent in study This is performance finance and variables its independence is is GCG (Good Corporate Governance). The method used is documentation and data analysis using analysis statistics descriptive . The test used is the Shapiro-Wilks normality test and the Mann-Whitney difference test using SPSS test tool . Based on the Mann-Whitney test shows that there is the difference in GCG (Good Corporate Governance) on the DPS ( Sharia Supervisory Board) indicator and the ROA (Return on Asset) indicator of Malaysian Islamic banks is greater superior compared to with Islamic banks Indonesia . Research This conclude that GCG (Good Corporate Governance) can increase performance finance and banking ROA (Return on Asset) sharia in Indonesia and Malaysia.